UNIT 26.3 RNA Interference in Caenorhabditis elegans. Issue 1 (5th January 2015) - Conte, Darryl; MacNeil, Lesley T.; Walhout, Albertha J.M.; Mello, Craig C.
Abstract : RNAi has become an essential tool in C. elegans research. This unit describes procedures for RNAi in C. elegans by microinjecting with dsRNA, feeding with bacteria expressing dsRNA, and soaking in dsRNA solution, as well as high‐throughput methods for RNAi‐based screens. © 2015 by John Wiley & Sons, Inc.